Frequency and management of respiratory incidents in invasive home ventilation. (August 2013) - Stieglitz, Sven; George, Sandhya; Priegnitz, Christina; Hagmeyer, Lars; Randerath, Winfried
There has been a rise in the number of patients requiring long-term ventilation, both in the in-hospital and the out-of-hospital setting. Despite this, little is known about the subsequent clinical course of these patients following hospital discharge. The purpose of this study was to determine the frequency and management of respiratory incidents in patients with invasive out-of-hospital ventilation living in a nursing home allied to a weaning centre. We evaluated retrospectively the protocols that are used to monitor the patients over a period of 2 months. The average time from hospital discharge was 386 ± 330 days. Of the total 17 patients, 9 (53%) patients remained free from any respiratory incidents, while the remaining 8 (47%) patients were responsible for a total of 95 respiratory incidents. Patients that suffered respiratory incidents had been ventilated at home for an average of 194 days, while the others were receiving out-of-hospital ventilation for an average of 557 days. Desaturation (17), dyspnoea (17) and reduced general condition (10) were the most common respiratory incidents. Also, the use of an Ambu bag (bag valve mask; 17), request for a pneumologist review (12) and replacement of the tracheal cannula (7) were the most common interventions. Respiratory incidents are common in invasive home mechanical ventilation, and so home mechanical ventilation needed to be organized safely. Being allied to a weaning centre helps to organize invasive home mechanical ventilation in a safe manner over the long-term ventilation.